2022
DOI: 10.52083/mzcm9500
|View full text |Cite
|
Sign up to set email alerts
|

Human unilateral bifid coronoid process – Report of a rare accidental radiographic finding

Abstract: Routine panoramic radiographic evaluations reveal morphological differences in the maxillofacial structures, particularly the mandible. Although bifid condyle variants are prevalent, bifid coronoid processes are rarely reported. Here a regular digital Orthopantomograph (OPG) was advised for the patient’s routine dental care, which revealed the presence of a unilateral bifid coronoid process on the right side of the jaw, which was confirmed with Cone Beam Computed Tomography (CBCT). This is notable, because it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Lundquist and Wege reported two normally formed coronoid processes, referred to as the double coronoid process, in a 41-year-old white male on the right side of the mandible [ 13 ]. Patil et al found a unilateral bifid coronoid process on the right side of the jaw in a 58-year-old male, which was an incidental finding on the panoramic image that was later confirmed by CBCT [ 2 ]. de Gittins et al reported a case of the double coronoid process in a 61-year-old female on the left side of the jaw.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Lundquist and Wege reported two normally formed coronoid processes, referred to as the double coronoid process, in a 41-year-old white male on the right side of the mandible [ 13 ]. Patil et al found a unilateral bifid coronoid process on the right side of the jaw in a 58-year-old male, which was an incidental finding on the panoramic image that was later confirmed by CBCT [ 2 ]. de Gittins et al reported a case of the double coronoid process in a 61-year-old female on the left side of the jaw.…”
Section: Discussionmentioning
confidence: 99%
“…The ramus is the vertical part that unites to the body near the angle of the mandible. The superior aspect of the ramus has two processes named coronoid and condylar process [ 2 ]. The coronoid process of the mandible is a triangular plate of bone that projects upward and slightly forward [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations